The Comparative Effectiveness of Vasoactive Treatments for Hepatorenal Syndrome: A Systematic Review and Network Meta-Analysis*. Issue 10 (12th September 2022) - Pitre, Tyler; Kiflen, Michel; Helmeczi, Wryan; Dionne, Joanna C.; Rewa, Oleksa; Bagshaw, Sean M.; Needham-Nethercott, Natalie; Alhazzani, Waleed; Zeraatkar, Dena; Rochwerg, Bram
Abstract : OBJECTIVE: Hepatorenal syndrome (HRS) is associated with high rates of morbidity and mortality. Evidence examining commonly used drug treatments remains uncertain. We assessed the comparative effectiveness of inpatient treatments for HRS by performing a network meta-analysis of randomized clinical trials (RCTs). DATA SOURCES: We searched MEDLINE, Embase, Cochrane Central Register of Controlled Trials, Medline In-Process & Other Non-Indexed Citations, Scopus, and Web of Science from inception. STUDY SELECTION AND DATA EXTRACTION: Pairs of reviewers independently identified eligible RCTs that enrolled patients with type 1 or 2 HRS. Pairs of reviewers independently extracted data. DATA SYNTHESIS: We assessed risk of bias using the Cochrane tool for RCTs and certainty of evidence using the Grading of Recommendations, Assessment, Development and Evaluations approach. Our main outcomes are all-cause mortality, HRS reversal, and serious adverse events. Of 3, 079 citations, we included 26 RCTs examining 1, 736 patients. Based on pooled analysis, terlipressin increases HRS reversal compared with placebo (142 reversals per 1, 000 [95% CI, >87.7 to >210.9]; high certainty). Norepinephrine (112.7 reversals per 1, 000 [95% CI, 52.6 to >192.3]) may increase HRS reversal compared with placebo (low certainty). The effect of midodrine+octreotide (67.8 reversals per 1, 000 [95% CI, <2.8 to >177.4]; very low) on HRS reversal is uncertain. Terlipressin may reduce mortality compared with placebo (93.7 fewer deaths [95% CI, 168.7 to <12.5]; low certainty). Terlipressin probably increases the risk of serious adverse events compared with placebo (20.4 more events per 1, 000 [95% CI, <5.1 to >51]; moderate certainty). CONCLUSIONS: Terlipressin increases HRS reversal compared with placebo. Terlipressin may reduce mortality. Until access to terlipressin improves, initial norepinephrine administration may be more appropriate than initial trial with midodrine+octreotide. Our review has the potential to inform future guideline and practice in the treatment of HRS.